Preparation method of solid supercapacitor

By using olefinamide derivatives to treat activated carbon electrodes and polymerizing solid electrolytes in situ, the interfacial side reactions and poor contact problems are solved, and the energy density, power density and wide temperature domain performance of solid supercapacitors are improved, significantly improving the Its safety and stability are achieved.

CN119170423APending Publication Date: 2024-12-20XIAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411455897.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing solid-state supercapacitors have interface side reactions and poor contact problems in high voltage and high temperature environments, resulting in difficulty in taking into account both energy density and power density, short service life and high safety risks.

Method used

By mixing activated carbon powder and olefinamide derivative in deionized water, a purified activated carbon electrode is formed, and a polymerization reaction is initiated during the electrode production process to form polyolefinamide as a binder; at the same time, the olefinamide derivative and ionic liquid are used to form the olefinamide derivative. The capacitor is polymerized in situ to form a solid electrolyte to ensure compatibility and interface stability between the electrode and the electrolyte.

Benefits of technology

It improves the cyclic stability and power responsiveness of solid-state supercapacitors, enhances the interface contact between the electrode and the electrolyte, shortens the ion diffusion path, improves the energy output and power characteristics, and has high-temperature domain stability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170423A_ABST
    Figure CN119170423A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a solid supercapacitor. The preparation method comprises the following steps: firstly, pretreating activated carbon by taking an olefin amide derivative carrying hydroxyl as an impurity removal agent; then adding the polyolefin amide as an electrode auxiliary material into an activated carbon electrode, and forming a polyolefin amide derivative through a polymerization reaction to play a role of a binder; and finally, adding the polymer monomer into an ionic liquid electrolyte solution, and forming the solid electrolyte through in-situ polymerization. The olefin amide derivative is used for three purposes, the defects of unstable interface and poor contact of a traditional solid-state device can be effectively overcome, and the constructed solid-state supercapacitor has the outstanding advantages of being high in working voltage and energy density, good in output power characteristic, wide in temperature range, high in safety and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitors, and in particular to a method for preparing a solid-state supercapacitor. Background Art

[0002] Supercapacitors have outstanding advantages such as high power density, long service life, and good low-temperature performance. However, their performance deteriorates severely under high voltage and high temperature environments, which hinders their large-scale promotion and application.

[0003] This is mainly due to: 1) Commercially available activated carbon electrode materials inevitably adsorb / retain various metals, halogens, moisture and other impurities, and carry unstable surface groups, which can easily cause irreversible interfacial side reactions under high pressure and high temperature; 2) Commercial electrolytes composed of quaternary ammonium salts dissolved in solvents such as acetonitrile have poor electrochemical and thermodynamic stability. High pressure and high temperature environments can lead to electrolyte decomposition, volatilization, gas production and even combustion risks, especially the interaction between the electrolyte and impurities and groups on the electrode surface, which is more likely to catalyze the degradation of the electrolyte.

[0004] Ionic liquids have the advantages of good thermal stability, wide electrochemical window, and high ionic conductivity, making them an ideal choice for supercapacitor electrolytes. If ionic liquids are combined with polymer skeletons to construct solid electrolytes, the reactivity of the electrolyte can be further reduced, reducing the decomposition and gas production of the electrolyte under high pressure and high temperature, while solving the leakage and corrosion problems of the electrolyte. Therefore, the solid-state supercapacitors constructed are more reliable and stable, and are more flexible in structural design and can adapt to complex application scenarios.

[0005] However, the contact performance between solid electrolyte and activated carbon electrode is poor, resulting in a significant decrease in the ion transfer efficiency between the electrode and electrolyte interface compared to liquid electrolyte, which greatly affects the energy output and power characteristics of solid supercapacitors. Moreover, the interfacial side reactions caused by impurities carried by activated carbon still exist in solid supercapacitors, which is particularly evident under high pressure and high temperature conditions.

[0006] In summary, the key defects of existing solid-state supercapacitors are interface side reactions and poor contact. The above defects make it difficult to balance the energy density and power density of solid-state supercapacitors, especially under high pressure and high temperature conditions, with short service life and great safety risks. Summary of the invention

[0007] In order to overcome the above technical problems, the purpose of the present invention is to provide a method for preparing a solid-state supercapacitor, which aims to improve the compatibility of the activated carbon electrode and the solid electrolyte, curb the interfacial side reactions, improve the interfacial contact and ion transport capacity, thereby improving the overall performance of the solid-state supercapacitor.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A method for preparing a solid-state supercapacitor, comprising:

[0010] S1: fully mixing the activated carbon powder and the olefin amide derivative in deionized water, collecting the solid phase by solid-liquid separation, washing with deionized water, and drying to obtain purified activated carbon powder;

[0011] S2: Evenly mix the purified activated carbon powder, the conductive agent, the olefin amide derivative, and the initiator in deionized water, and initiate preliminary polymerization at a moderately high temperature to form a viscous electrode slurry;

[0012] S3: coating the viscous electrode slurry on the surface of the conductive current collector, maintaining a moderately high temperature to further complete the polymerization reaction, and drying to obtain a purified activated carbon electrode;

[0013] S4 dissolving the olefin amide derivative and the initiator in the ionic liquid to form an electrolyte precursor solution;

[0014] S5 stacks the purified activated carbon electrode, the diaphragm, and the purified activated carbon electrode in sequence, injects the electrolyte precursor solution, applies negative pressure to allow the solution to fully penetrate the electrode and the diaphragm, and seals and assembles them into a liquid supercapacitor.

[0015] S6 places the liquid supercapacitor in a moderately high temperature environment, causing the electrolyte precursor solution to polymerize in situ inside the supercapacitor to form a solid supercapacitor.

[0016] The structural formula of the olefin amide derivative is:

[0017]

[0018] Among them, R1 is any one of H and hydrocarbon group; R2 is any one of hydrocarbon group and ether group, or R2 is vacant; R3 and R4 are any one of H and hydrocarbon group; R5 and R6 are any one of H and hydroxyl group, and at least one of R5 and R6 is hydroxyl group; when R3 is H, R5 is vacant; when R4 is H, R6 is vacant.

[0019] The initiator includes at least one of potassium persulfate (KPS), ammonium persulfate (APS), azobisisobutyronitrile (AIBN), and benzoyl peroxide (BPO).

[0020] The conductive agent includes at least one of nano carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanofiber, carbon nanotube and graphene.

[0021] The ionic liquid includes a cation and an anion, wherein the cation includes at least one of imidazole, quaternary ammonium, pyrrole, piperidine, pyridine, and quaternary phosphine;

[0022] The anions include NO3 - 、ODFB - 、BOB - PF6 - TFSI - 、BF4 - 、ClO4 - 、FSI - BETI - CF3SO3 - , Tf - ,OTf - BC2O4F2 - 、N(FSO2)2 - 、N(CF3SO2)2 - 、FAP - 、FAB - TFSM - At least one of .

[0023] More specifically, the cation of the ionic liquid includes 1-ethyl-3-methylimidazole (EMIM + )、1-methyl-3-ethylimidazole (EMI + )、1-methyl-3-butylimidazole (BMI + )、1-methyl-3-vinylimidazole (EVI + ), N-butyl-N-methylpyrrolidine (Pyr 14 + )

[0024] The anion of the ionic liquid includes TFSI - 、BF4 - 、FSI - 、ODFB - At least one of .

[0025] At least one of the viscous electrode slurry and the electrolyte precursor solution also contains a crosslinking agent, and the crosslinking agent includes at least one of acrylamide (AM), methylenebisacrylamide (MBA), acrylic acid (AA), carboxymethyl cellulose (CMC), ethylene glycol dimethacrylate (EGDMA), methyl acrylate, alginate, and chitosan.

[0026] In the step S1, the mass ratio of the original activated carbon powder and the olefin amide derivative is (70-96):(4-30), and the mixing time is 12-36 hours.

[0027] In the step S2, the mass ratio of the purified activated carbon powder, the conductive agent, the olefin amide derivative, and the initiator is (70-95):(2-10):(2-20):(0.2-5).

[0028] In S2, the polymerization temperature is (30-80°C) and the polymerization time is (0.5-6)h;

[0029] In S3, the polymerization temperature is (30-80°C) and the polymerization time is (1-12) hours;

[0030] In the above S6, the polymerization temperature is (30-80°C) and the polymerization time is (2-24) hours.

[0031] In the step S4, the mass ratio of the olefin amide derivative, the initiator, and the ionic liquid is (2-20):(0.2-5):(75-98).

[0032] In the step S5, the pressure of the negative pressure applied is (-0.07 to -0.09) mPa, and the time of applying the negative pressure is (0.5 to 2) h.

[0033] The beneficial effects of the present invention are:

[0034] First, the present invention uses olefin amide derivatives to pretreat the original activated carbon, reduce the impurity content in the activated carbon powder and passivate the unstable groups on the surface, which can reduce the interface side reactions between the activated carbon and the electrolyte and improve the cycle stability of the capacitor under high pressure and high temperature conditions. Then, the olefin amide derivative monomer is added to the activated carbon electrode to initiate a polymerization reaction during the electrode manufacturing process. The formed polyolefin amide has strong adhesion and can be used as an aqueous binder to stabilize the electrode structure. Finally, the olefin amide derivative monomer is used again to prepare a solid electrolyte by in-situ polymerization inside the capacitor. Since the electrode and the electrolyte contain the same polymer matrix, the compatibility of the two is guaranteed, the interface stability is further improved, and the in-situ polymerization mechanism can realize the bulk penetration of the electrolyte solution in the electrode, enhance the interface contact between the electrode and the electrolyte, shorten the ion diffusion path, and improve the power responsiveness of the solid capacitor.

[0035] Furthermore, the hydroxyl modified group carried by the olefin amide derivative has a purification effect, and can effectively remove some metal impurities and / or acidic functional groups on the surface of activated carbon through hydrogen bonding, polar adsorption, chemical / neutralization reaction, etc., and the modified group can also realize chemical cross-linking inside the olefin amide skeleton; the olefin amide derivative has strong water solubility due to carrying hydrophilic amide groups, and also has good affinity with ionic liquids, and can be evenly dispersed in both aqueous solutions and ionic liquids; the olefin amide derivative has polymerization properties due to carrying unsaturated C=C double bonds, and polymerization reactions are easy to occur under light / heat conditions.

[0036] Furthermore, the initiator can attack the unsaturated bonds of the olefin amide derivatives under moderately high temperature conditions to initiate free radical polymerization, and has the advantages of high polymerization efficiency and controllable polymerization reaction. The amide polymers formed after the initiation polymerization of the olefin amide derivatives have water solubility and strong adhesion, and are suitable for use as aqueous binders for activated carbon electrodes.

[0037] Furthermore, the conductive agent can improve the conductivity of the activated carbon material and enhance the electrode power characteristics.

[0038] Furthermore, the ionic liquid has the advantages of electrochemical stability and thermal stability, and can provide a wide electrochemical stability window, while reducing high-temperature volatilization and thermal decomposition of the electrolyte, thereby ensuring the high-voltage and high-temperature performance of the capacitor.

[0039] Furthermore, a cross-linking agent may be further introduced into the viscous electrode slurry and the electrolyte precursor solution to construct a three-dimensional interpenetrating cross-linked network through polymerization reaction, thereby enhancing the mechanical strength and film-forming performance of the polymer skeleton.

[0040] Furthermore, in order to give full play to the impurity-removing effect of the modified olefin aniline, the present invention limits the mass ratio and mixing time of the original activated carbon powder and the olefin amide derivative in step S1.

[0041] Furthermore, in order to construct a purified activated carbon electrode with stable structure, uniform properties and good conductivity, and to ensure that the olefin amide derivative reacts completely with the initiator, this project defines the mass ratio of purified activated carbon powder, conductive agent, olefin amide derivative and initiator in steps S2 and S3, and determines the polymerization temperature and time. It should be noted that the polymerization time defined in step S2 is to temporarily form a slurry with moderate viscosity in the first stage of the polymerization reaction, so as to facilitate subsequent slurry coating.

[0042] Furthermore, in order to promote the complete reaction between the olefin amide derivative and the initiator in the electrolyte precursor solution and take into account the ionic conductivity and mechanical / film-forming properties of the solid electrolyte, the present invention limits the mass ratio of the olefin amide derivative, the initiator, and the ionic liquid, as well as the polymerization reaction temperature and time in step S4.

[0043] Furthermore, in order to ensure that the electrolyte precursor solution fully infiltrates the electrodes and enhances the interface contact, the present invention limits the pressure and time of applying negative pressure in step S5.

[0044] In summary, the preparation method disclosed in the present invention can effectively solve the interface instability and poor contact defects existing in the use of traditional solid-state supercapacitors. The constructed solid-state supercapacitor has outstanding advantages such as high operating voltage and energy density, good output power characteristics, wide temperature range, high safety, etc., and has significant innovation and technological progress. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a cycle performance diagram of the solid-state supercapacitor prepared in Example 1.

[0046] Figure 2 This is a cycle performance diagram of the traditional solid-state supercapacitor prepared in Comparative Example 1. DETAILED DESCRIPTION

[0047] The present invention will be further described in detail below in conjunction with the accompanying drawings.

[0048] Example 1

[0049] A preparation method of a solid-state supercapacitor is as follows: S1) mixing activated carbon and N-hydroxymethyl acrylamide in a mass ratio of 90:10 in deionized water and stirring for 24 hours, collecting the precipitate by centrifugal separation, washing with deionized water, and vacuum drying to obtain purified activated carbon powder; S2) uniformly mixing the purified activated carbon powder, nano carbon black, N-hydroxymethyl acrylamide, and potassium persulfate in a mass ratio of 90:4.5:5:0.5 in deionized water, preliminarily polymerizing at 40°C for 2 hours to form a viscous electrode slurry; S3) coating the viscous electrode slurry on the surface of corroded aluminum foil, The mixture was further polymerized at 60°C for 8h, and a purified activated carbon electrode was obtained after vacuum drying; S4) N-hydroxymethyl acrylamide, potassium persulfate, and EMITFSI were mixed uniformly in a mass ratio of 5:0.5:94.5 to form an electrolyte precursor solution; S5) The purified activated carbon electrode, the diaphragm, and the purified activated carbon electrode were stacked in sequence, the electrolyte precursor solution was injected, and after maintaining at -0.08mPa for 0.5h, they were sealed and assembled into a cylindrical liquid supercapacitor; S6) The cylindrical liquid supercapacitor was placed in an environment of 60°C for 12h to induce in-situ polymerization to form a solid-state supercapacitor.

[0050] Example 2

[0051] A method for preparing a solid-state supercapacitor, wherein the olefin amide derivative is N-(2-hydroxypropyl) acrylamide (NHA), the initiator is AIBN, the ionic liquid is Pyr14TFSI, and the rest is the same as in Example 1.

[0052] Example 3

[0053] A method for preparing a solid-state supercapacitor, wherein the electrolyte precursor solution further contains a crosslinking agent AA, and the mass ratio of N-hydroxymethyl acrylamide, potassium persulfate, EMITFSI, and AA in the electrolyte precursor solution is 6:1:90:3, and the rest is the same as in Example 1.

[0054] Example 4

[0055] A method for preparing a solid supercapacitor: S1) the mass ratio of activated carbon to NHA is 95:5, and the mixing time is 36 hours; S2) in a viscous electrode slurry, the mass ratio of purified activated carbon powder, mixed conductive agent (carbon black to carbon nanotube mass ratio 90:10), NHA, and AIBN is 94.7:2.5:2.5:0.2, and preliminary polymerization is carried out at 50°C for 3 hours; S3) after the viscous electrode slurry is coated on the surface of aluminum foil, further polymerization is carried out at 80°C for 6 hours; S4) in an electrolyte precursor solution, the mass ratio of NHA, AIBN, and Pyr14TFSI is 2.5:0.2:97.3; S5) after injecting the electrolyte precursor solution, it is kept at -0.07mPa for 1 hour; S6) it is placed at 80°C for 10 hours to form a solid supercapacitor. The rest is the same as Example 2.

[0056] Comparative Example 1

[0057] A solid supercapacitor is manufactured according to the following steps: 1) evenly mixing activated carbon, nano carbon black, CMC and SBR in deionized water at a mass ratio of 90:5:2.5:2.5, and coating the mixture on the surface of corroded aluminum foil; 2) evenly mixing PVDF-HFP and EMITFSI in DMF at a mass ratio of 20:80, coating the obtained solution on the surface of a flat mold, and forming an independent solid electrolyte membrane after solvent volatilization and demoulding; 3) stacking an activated carbon electrode, a solid electrolyte membrane and an activated carbon electrode in sequence to assemble into a cylindrical solid supercapacitor.

[0058] The supercapacitors prepared in Example 1 and Comparative Example 1 were subjected to charge and discharge tests, with a voltage window of 0-3V, a charge and discharge current of 10A, a test temperature of 60°C, and a cycle of 10,000 cycles. The cycle performance curves are shown as follows: Figure 1 and Figure 2 As shown, the specific test results are summarized in Table 1 (energy density and power density are calculated based on the total weight of the capacitor). It can be seen from the chart that compared with the solid-state supercapacitors made by the traditional method, the solid-state supercapacitors made by the method of the present invention have obvious advantages in energy density, power density, internal resistance, cycle stability and safety performance under high temperature and high pressure working conditions, and the comprehensive performance is more excellent.

[0059] Table 1 Test results of embodiments and comparative examples

[0060]

[0061] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a solid-state supercapacitor, characterized in that: include: S1: fully mixing the activated carbon powder and the olefin amide derivative in deionized water, collecting the solid phase by solid-liquid separation, washing with deionized water, and drying to obtain purified activated carbon powder; S2: Evenly mix the purified activated carbon powder, the conductive agent, the olefin amide derivative, and the initiator in deionized water, and initiate preliminary polymerization at a moderately high temperature to form a viscous electrode slurry; S3: coating the viscous electrode slurry on the surface of the conductive current collector, maintaining a moderately high temperature to further complete the polymerization reaction, and drying to obtain a purified activated carbon electrode; S4 dissolving the olefin amide derivative and the initiator in the ionic liquid to form an electrolyte precursor solution; S5 stacks the purified activated carbon electrode, the diaphragm, and the purified activated carbon electrode in sequence, injects the electrolyte precursor solution, applies negative pressure to allow the solution to fully penetrate the electrode and the diaphragm, and seals and assembles them into a liquid supercapacitor. S6 places the liquid supercapacitor in a moderately high temperature environment, causing the electrolyte precursor solution to polymerize in situ inside the supercapacitor to form a solid supercapacitor.

2. The method for preparing a solid-state supercapacitor according to claim 1, characterized in that: The structural formula of the olefin amide derivative is: Among them, R1 is any one of H and hydrocarbon group; R2 is any one of hydrocarbon group and ether group, or R2 is vacant; R3 and R4 are any one of H and hydrocarbon group; R5 and R6 are any one of H and hydroxyl group, and at least one of R5 and R6 is hydroxyl group; when R3 is H, R5 is vacant; when R4 is H, R6 is vacant.

3. The method for preparing a solid supercapacitor according to claim 1, characterized in that: The initiator includes at least one of potassium persulfate (KPS), ammonium persulfate (APS), azobisisobutyronitrile (AIBN), and benzoyl peroxide (BPO).

4. The method for preparing a solid supercapacitor according to claim 1, characterized in that: The conductive agent includes at least one of nano carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanofiber, carbon nanotube and graphene.

5. The method for preparing a solid supercapacitor according to claim 1, characterized in that: The ionic liquid includes a cation and an anion, wherein the cation includes at least one of imidazole, quaternary ammonium, pyrrole, piperidine, pyridine, and quaternary phosphine; The anions include NO3 - 、ODFB - 、BOB - PF6 - TFSI - 、BF4 - 、ClO4 - 、FSI - BETI - CF3SO3 - , Tf - ,OTf - BC2O4F2 - 、N(FSO2)2 - 、N(CF3SO2)2 - 、FAP - 、FAB - TFSM - At least one of .

6. The method for preparing a solid supercapacitor according to claim 1, characterized in that: At least one of the viscous electrode slurry and the electrolyte precursor solution also contains a crosslinking agent, and the crosslinking agent includes at least one of acrylamide (AM), methylenebisacrylamide (MBA), acrylic acid (AA), carboxymethyl cellulose (CMC), ethylene glycol dimethacrylate (EGDMA), methyl acrylate, alginate, and chitosan.

7. The method for preparing a solid supercapacitor according to claim 1, characterized in that: In the step S1, the mass ratio of activated carbon powder to olefin amide derivative is (70-96):(4-30), and the mixing time is 12-36 hours.

8. The method for preparing a solid supercapacitor according to claim 1, characterized in that: In the step S2, the mass ratio of the purified activated carbon powder, the conductive agent, the olefin amide derivative, and the initiator is (70-95):(2-10):(2-20):(0.2-5).

9. The method for preparing a solid supercapacitor according to claim 1, characterized in that: In the step S2, the polymerization temperature is (30-80°C) and the polymerization time is (0.5-6) ​​hours; In the step S3, the polymerization temperature is (30-80°C) and the polymerization time is (1-12) hours; In the step S6, the polymerization temperature is (30-80° C.) and the polymerization time is (2-24) h.

10. The method for preparing a solid supercapacitor according to claim 1, characterized in that: In the step S4, the mass ratio of the olefin amide derivative, the initiator, and the ionic liquid is (2-20):(0.2-5):(75-98); In the step S5, the pressure of the negative pressure applied is (-0.07 to -0.09) mPa, and the time of applying the negative pressure is (0.5 to 2) h.